242 BONE AND BODY COMPOSITION IN INFANTS AND YOUNG CHILDREN: CROSS-VALIDATION OF NON-INVASIVE METHODS. (1st January 2006) - Huntington, M. A.; Slater, H.; Wilkinson, R.; Hammond, S.; Winder, S.; Clarke, K. K.; Chan, G. M.; Moyer-Mileur, L. J.
Abstract : Background: Measurement of physical growth and body composition are used to monitor growth and nutrition status in infants. Bioelectrical impedance analysis (BIA), quantitative ultrasound (QUS), and dual energy x-ray absorptiometry (DEXA) are non-invasive methods that have been used independently in neonates to determine bone and body composition. Cross-validation of these methods in infants has not been reported. Purpose: To cross-validate three non-invasive methods (BIA, QUS, and DEXA) of bone and body composition in healthy infants and children ages 0-36 months. Design: A cross-sectional sample of healthy white, non-Hispanic ( n = 78; 35 M) and Hispanic ( n = 91; 50 M) infants and young children stratified by age (0 M, n = 51; 6 M, n = 39; 12 M, n = 45, and 36 M, n = 34) were studied. Height, weight, total body water (TBW = 0.76 + 0.18 (ht 2 /z) + 0.39Wt) by BIA (Quantum II, RJL Systems), and speed of sound of the tibia (SOS, MHz) by QUS (Sunlight Omnisense 7000) were measured. Bone area, mineral content, and density (BA, cm 2, BMC, g and BMD, g/cm 2 ) of the proximal forearm by peripheral DEXA (pDEXA, Norland Medical Systems) were determined for all newborn infants and whole body DEXA (Hologic 4500A) was obtained in a subset of subjects at 0 M ( n = 22) and 36 M ( n = 5). The strength of the relationships between BIA and DEXA measures of fat-free mass and QUS and DEXA measures of bone were evaluated by Pearson correlations. Results: Weight and height did not differ by gender although mean height was greater in white, non-Hispanic subjects (65.0 ± 2.9 cm vs 58.2 ± 11.6 cm; p = .01). Age, weight, and height were positively associated with TBW, SOS, and whole body FFM by DEXA ( r 2 = .73-.99, p = .001). Whole body fat-free mass by DEXA was strongly related to TBW by BIA ( r 2 = .99, p = .001). Tibia bone strength by QUS was positively correlated with both proximal forearm and whole body BMC ( r 2 = .72, p = .001) and inversely related to whole body BMD ( r 2 = -.60, p = .001). Conclusion: BIA and QUS appear to provide valid assessments of lean and bone mass, respectively, in healthy infants and young children. Furthermore, the absence of radiation exposure, decreased cost, and portability are potential advantages of the BIA and QUS methods over x-ray technologies.